Recent findings of the declining frog Pleurodema bibroni Tschudi, 1838 (Anura: Leiuperidae) in Uruguay - Kolenc, Francisco (2012)
Fil: Kolenc, Francisco. Museo Nacional de Historia Natural de Montevideo; Uruguay